Work till you drop - Miller, Charles (Australia : BBC, 2003)
Describes the growing crisis in England, where older people are discriminated against in the workplace, but are finding they need to work because of inadequate pensions. Some of this was due to company failures and the economic downturn in the 80's as well as lack of government planning
Series editor, Clive Edwards
Narrator: Adrian Chiles
DVD format
Keywords: Age discrimination in employment; Retirement income